HUBUNGAN ANTARA PRESTASI BELAJAR PENDIDIKAN SISTEM GANDA DENGAN MOTIVASI SISWA MEMASUKI DUNIA KERJA BIDANG TEKNIK KONSTRUKSI BATU DAN BETON - Tri Puspita Sari; Daryati Daryati; Dadang Suyadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
This research aims to get the relationship between learning achievement of Double System Education and student’s motivation to involve in the field of masonry and concrete construction working environment.The duration of research is conducted in May 24th – 25th 2012. SMK Negeri 4 Jakarta is chosen to be the place of conducting this research. The population of this research is the students of the second and third grade majoring in masonry and concrete construction who have performed Double System Education activity. The sample of this research is the second grade students of SMK Negeri 4 Jakarta majoring in masonry and concrete construction who have performed Double System Education activity. The research method is surveying using correlation approach. The questionnaire consists of 62 items of statement and it is tested to 10 students in the third grade of SMK Negeri 4 Jakarta majoring in masonry and concrete construction. After the test, there is a valid instrument for data collecting in the sample and number of valid items. Finally, there are 41 valid items. Either learning achievement variable of Double System Education or student’s motivation to involve in the working environment has shown normal distribution. Coefficient of correlation (rxy) equals 0.85. Regression equation between learning achievement of Double System Education and student’s motivation to involve in the working environment is Ŷ = 17.09 + 1.67X. The hypothesis results from the table ttable and calculation thitung are 2.09 and 7.22 respectively, Ho is rejected and Ha is accepted. The result shows that there is a positive and significant relationship between learning achievement variable of Double System Education or student’s motivation to involve in the field of masonry and concrete working environment